2011
DOI: 10.1038/bjc.2011.109
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic impact of serum HE4 detection in endometrial carcinoma patients

Abstract: Background:To date, no good marker for screening or disease monitoring of endometrial cancer (EC) is available. The aims of this study were to investigate HE4 gene, protein expression and serum HE4 (sHE4) levels in a panel of ECs and normal endometria (NEs) and to correlate sHE4 with patient clinicopathological characteristics and prognosis.Methods:Using quantitative real-time PCR we tested 46 ECs and 20 NEs for HE4 gene expression. Protein expression was analysed by immunohistochemistry on tissue microarrays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

29
149
2
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(191 citation statements)
references
References 25 publications
(33 reference statements)
29
149
2
7
Order By: Relevance
“…Multiple studies have demonstrated that serum HE4 is a useful tumor biomarker of EC (17,28). HE4 expression levels correlates positively with aggressive phenotype, tumor size and myometrial invasion of EC (11,18,26,27), but inversely with overall EC patients survival (26,28,29). We have reported that in EC cell culture and mouse xenograft model forced overexpression of HE4 resulted in more aggressive phenotypes (31).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Multiple studies have demonstrated that serum HE4 is a useful tumor biomarker of EC (17,28). HE4 expression levels correlates positively with aggressive phenotype, tumor size and myometrial invasion of EC (11,18,26,27), but inversely with overall EC patients survival (26,28,29). We have reported that in EC cell culture and mouse xenograft model forced overexpression of HE4 resulted in more aggressive phenotypes (31).…”
Section: Discussionmentioning
confidence: 94%
“…Though HE4 is upregulated in many malignancies, there is a limited knowledge on the function of HE4 in cancer development. In endometrial cancers, higher HE4 levels positively correlate with more aggressive phenotype, larger tumor size and myometrial invasion (26,27), and negatively correlate with the overall survival, disease-free survival and progression-free survival (12,26,28,29). Using endometrial cancer cell lines and mouse ectopic subcutaneous cancer models, this and other groups have shown that overexpression of HE4 led to increased cell proliferation and faster cancer progression.…”
Section: Introductionmentioning
confidence: 99%
“…HE4 and CA125 have been widely used in routine management of OC [10]. Recent studies have considered the role of HE4 in the diagnosis, staging and prognosis of EC [11][12][13]. In this study, we present our experience in the assessment of the role of HE4 and CA125 in differentiating between malignant and non-malignant endometrial pathologies.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review analyzed five case-control studies covering a total of 1221 patients (667 endometrial cancers and 554 controls) [20]. Two studies without a clear documentation of cutoff values reported the same specificity of 90%, while the sensitivities are 95% and 98%, respectively [21,22]. Other three studies using 50-70 pM cutoff values reported 78.8% sensitivity and 100% specificity [23][24][25].…”
Section: Introductionmentioning
confidence: 99%